trans-Tetraaquabis[1,3-bis(4-pyridyl)propane-κN]cobalt(II) biphenyl-4,4′-disulfonate monohydrate - Liu, Guang-Xiang (International Union of Crystallography, 2011)
In the title compound, [Co(C13H14N2)2(H2O)4](C12H8O6S2)·H2O, the cation, anion and uncoordinated water molecule have crystallographically imposed twofold symmetry. The cobalt(II) atom exhibits a slightly distorted octahedral coordination geometry provided by two N atoms from two 1,3-bis(4-pyridyl)propane ligands and the O atoms from four water molecules. The dihedral angle between the pyridine rings in the ligand is 86.14 (11)°, whereas the dihedral angle formed by the symmetry-related benzene rings in the anion is 35.81 (12)°. In the crystal, cations, anions and water molecules are linked into layers parallel to the ac plane by O—H⋯O and O—H⋯N hydrogen-bond interactions. The layers are further connected into a three-dimensional network by C—H⋯O hydrogen bonds.